Biotelemetry Using Human Area Networking - Godhavari, T; Urvasi, D (International Journal of Engineering and Technology, 2018)
Human Body Communication (HBC) is a novel communication method between devices which use human body as a transmission medium. This idea is mostly based on the concept of wireless biomedical monitoring system. The on-body sensor nodes can monitor vital signs of a human body and use the body as a transmission medium. This technology is convenient for long durations of clinical monitoring with the option of more mobility and freedom for the user. Biotelemetry is remote monitoring, measuring and recording of a living organismâ€™s function, activity or condition. Network of sensor nodes placed on or implanted inside the body of a subject is called Human Body Area Network (HAN). RedTacton is a user-friendly pervasive technology that establishes a communication between human body and devices in a closer proximity. This paper proclaims model of a human area networking technologies that enables communication by means of â€œTouchingâ€. Redtacton technology was implemented to overcome the weak radio signals, data speeds and security â€“risks on unwanted signal interceptions. Here, human body is the transmitting medium supporting IEEE 802.3 half-duplex communication at 10 Mbits/s. RedTacton uses the minute electric field generated by human body as a medium to transmit the data.Â Â